Isra’ and Mi‘raj from Modern Perspective: An Analytical Study of Fazlur Rahman's views - Adam, Ibrahim Ilyasu (Journal of Quranic Sciences and Research, 2025)
This paper examines the concept of Isra’ and Mi‘raj from a modern perspective, giving special reference to Fazlur Rahman, a modernist and a controversial figure in Western academia. According to Islamic orthodoxy, Isra’ and Mi‘raj refer to two segments of the Prophet Muhammad's miraculous night journey from Mecca to Jerusalem and his subsequent ascension to heaven. The historicity of the journey, as well as its authenticity, however, has continued to be debatable.  While a majority of Muslim scholars consider the journey real and physical, Rahman argues that it is just a dream or vision, contending that a physical ascension to heaven is by no means possible. Furthermore, he denies the possibility of seeing angels physically condemning all traditions related to that as fictions. Indeed, this theory has generated criticism within academia and beyond. This paper critically analyses Rahman's views in the light of the authentic traditions, demonstrating that the journey is real and physical. Similarly, it establishes that Prophet Muhammad's Ascension is not a concocted narration as Rahman claims, but an authentic historical fact which constitutes an integral part of the Prophet’s message.